The Promoter's Liability for Concert Cancellations from the Perspective of the Consumer Protection Law - Angel Virgi Azzahra; Dadan Taufik Fathurohman (Riviera Publishing, 2026)
Concert cancellations by promoters have become a significant consumer protection issue in Indonesia, particularly when consumers experience financial losses due to unclear information, delayed refunds, or the absence of promoter accountability. This study aims to examine the legal liability of concert promoters for unilateral concert cancellations and to analyze the actions available to consumers in seeking legal protection and compensation. This research employed an empirical legal method with sociological and statutory approaches. Primary data were collected through interviews and communication with relevant parties, including consumers, the Consumer Dispute Resolution Agency (BPSK), and related authorities, while secondary data were obtained from laws, legal books, journal articles, and previous studies. The findings show that the purchase of concert tickets creates a contractual legal relationship between promoters and consumers. When promoters cancel concerts without clear reasons, fail to provide refunds, or neglect licensing obligations, such actions may constitute breach of contract and violations of Law No. 8 of 1999 on Consumer Protection. Consumers may pursue remedies through refund requests, BPSK mediation, conciliation, arbitration, civil lawsuits, or criminal reports when fraud is indicated. In conclusion, promoter liability is legally enforceable, but consumer protection remains weak due to limited accountability and low consumer awareness of formal legal remedies.